2021
DOI: 10.1016/j.prro.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy for Treatment of Soft Tissue Sarcoma in Adults: Executive Summary of an ASTRO Clinical Practice Guideline

Abstract: Sources of support: This work was funded by the American Society for Radiation Oncology. Disclosures: All task force members' disclosure statements were reviewed before being invited and were shared with other task force members throughout the guideline's development. Those disclosures are published within this report. Where potential conflicts were detected, remedial measures to address them were taken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 69 publications
(49 reference statements)
0
104
0
Order By: Relevance
“…For the final example, a more complex geometry with anisotropy in the tumor spread is introduced. The anisotropy can come from directional tissues that serve as highways for tumor cells, such as white matter tracts for brain tumors (corpus callosum) (Jordan et al, 2019), and muscle fibers for certain types of sarcoma (Salerno et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the final example, a more complex geometry with anisotropy in the tumor spread is introduced. The anisotropy can come from directional tissues that serve as highways for tumor cells, such as white matter tracts for brain tumors (corpus callosum) (Jordan et al, 2019), and muscle fibers for certain types of sarcoma (Salerno et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The art of defining the CTV has been described in textbooks (Grosu and Nieder, 2015). For specific disease sites, consensus guidelines have been developed (Niyazi et al, 2016;Grégoire et al, 2018;Wang et al, 2011;Salerno et al, 2021). They normally recommend expanding the GTV by a fixed margin, while avoiding anatomical barriers that serve as impenetrable walls for tumor cell spread (Shusharina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent retrospective review of the National Cancer Database revealed a survival benefit only in those with high-grade liposarcoma measuring greater than 10 cm receiving radiation in the adjuvant setting [ 109 ]. Additional details regarding dosing, target volumes, techniques, and the overall role of RT in RPS management are outlined in a 2021 review [ 110 ], and summarized within the 2021 American Society of Radiation Oncology clinical practice guidelines for soft-tissue sarcoma [ 111 ]. Further studies are needed to address subgroups of RPS most likely to benefit from adjunctive radiation therapy.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Consensus and target delineation guidelines for soft tissue sarcomas and retroperitoneal sarcomas provide a framework to promote standardization of quality of care delivered between referral and community centers. 14 In addition, many cooperative group protocols in the pediatric and adult setting for sarcoma require centralized quality assurance peer review prior to treatment, and adherence to protocol guidelines has been shown to result in improved outcomes. 15 In practice, with the increased access to referral centers via telehealth or through virtual sarcoma tumor boards, we can more provide timely radiotherapy recommendations, including often personal discussion with the treating community-based radiation oncologist, particularly when a photon or electron based treatment course is indicated which are more widely available technologies.…”
Section: Radiationmentioning
confidence: 99%